Hollow Microporous Organic Capsules Loaded with Highly Dispersed Pt Nanoparticles for Catalytic Applications. Issue 12 (21st May 2014) - Yang, Xinjia; Song, Kunpeng; Tan, Liangxiao; Hussain, Irshad; Li, Tao; Tan, Bien
<x xml:space="preserve">Abstract</x> Hollow microporous organic capsules embedded with small and monodisperse Pt nanoparticles (NPs) are designed and synthesized successfully. The transmission electron microscopy (TEM) results show that the materials with amine groups and a microporous structure act as a better support for obtaining highly dispersed Pt NPs in the micropores. After several successive catalytic reactions, the TEM and porous structure of the heterogeneous catalysts do not show any observable changes. The heterogeneous catalysts are highly stable in air and no decrease in activity is observed after the catalyst is exposed to air for several days. These heterogeneous catalysts exhibit excellent catalytic activity and recyclability potential, combined with mild conditions, and the possibility of using alcoholic reaction media for the nitroaromatic hydrogenation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>